Performance Analysis of Cement manufacturing Industry (International Journal of Engineering and Computer Science, 2017)
Growing concerns arise about energy consumption and its adverse environmental impact in recent years in India, which cause manufactures to establish energy management groups. The purpose of the Audit is to identify the performance of Energy Guzzlers and set the Energy Baseline for the facility. For finding out the energy baseline various testing has been performed. As per the current pattern there are numerous measures which will help facility to reduce their energy baseline in future. The results from the performance analysis of cement industry has been presented in this paper.